Empirical studies on software traceability: A mapping study. Issue 2 (30th June 2020) - Charalampidou, Sofia; Ampatzoglou, Apostolos; Karountzos, Evangelos; Avgeriou, Paris
Abstract: During the last decades, software traceability has been studied in a large number of studies, from different perspectives (e.g., how to create traces and what are its benefits). This large body of knowledge needs to be better explored and exploited by both practitioners and researchers: We need an overview of different aspects of traceability and a structured way to assess and compare existing work in order to extend it with new research or apply it in practice, Thus, we have conducted a secondary study on this large corpus of primary studies, focusing on empirical studies on software traceability, without setting any further restrictions in terms of investigating a specific domain or concrete artifacts. The study explores the goals of existing approaches and the empirical methods used for their evaluation. Its main contributions are the investigation of (a) the type of artifacts linked through traceability approaches; (b) the benefits of using artifact traceability approaches; (c) the ways of measuring their benefit; and (d) the research methods used. The results of the study suggest that (i) requirements artifacts are dominant in traceability; (ii) the research corpus focuses on the proposal of novel techniques for establishing traceability; and (iii) the main benefits are the improvement of software correctness and maintainability. Finally, although many studies include some empirical validation, there is still room for improvements and research methods that can be used more extensively. The obtained results are discussed under the prism of both researchers and practitioners and are compared against the state‐of‐the‐art.